2022
DOI: 10.1002/jat.4306
|View full text |Cite
|
Sign up to set email alerts
|

α‐Mangostin protects lipopolysaccharide‐stimulated nucleus pulposus cells against NLRP3 inflammasome‐mediated apoptosis via the NF‐κB pathway

Abstract: Intervertebral disc degeneration (IDD) is a common and chronic inflammatory disorder. α‐Mangostin exhibits a novel biological function against inflammation in various inflammatory diseases. Here, we aimed to explore the role of α‐mangostin in IDD using an in vitro cell model. Human nucleus pulposus cells (NPCs) were exposed to lipopolysaccharide (LPS) to induce inflammatory injury. Cell viability of NPCs was determined by CCK‐8 assay. ELISA was performed to examine the production of interleukin (IL)‐1β and IL‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Anfibatide could inhibit the expression of NLRP3, ASC, cleaved‐caspase‐1, Bax and cleaved‐caspase‐3, promoted the expression of Bcl‐2 in cerebral ischemia reperfusion in vivo and in vitro, which indicates that anfibatide could alleviate inflammation and apoptosis through inhibiting NF‐kappaB/NLRP3 axis 29 . Alpha‐mangostin exerted a protective effect on NLRP3 inflammasome‐mediated apoptosis in LPS‐induced NPCs through regulating NF‐κB signaling 30 . Our previous studies have demonstrated that the NLRP3 inflammasome is activated in CMECs, which plays a critical role in the pathophysiology of MI/R injury.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Anfibatide could inhibit the expression of NLRP3, ASC, cleaved‐caspase‐1, Bax and cleaved‐caspase‐3, promoted the expression of Bcl‐2 in cerebral ischemia reperfusion in vivo and in vitro, which indicates that anfibatide could alleviate inflammation and apoptosis through inhibiting NF‐kappaB/NLRP3 axis 29 . Alpha‐mangostin exerted a protective effect on NLRP3 inflammasome‐mediated apoptosis in LPS‐induced NPCs through regulating NF‐κB signaling 30 . Our previous studies have demonstrated that the NLRP3 inflammasome is activated in CMECs, which plays a critical role in the pathophysiology of MI/R injury.…”
Section: Discussionmentioning
confidence: 92%
“…29 Alpha-mangostin exerted a protective effect on NLRP3 inflammasome-mediated apoptosis in LPS-induced NPCs through regulating NF-κB signaling. 30 Our previous studies have demonstrated that the NLRP3 inflammasome is activated in CMECs, which plays a critical role in the pathophysiology of MI/R injury. Furthermore, NLRP3 inflammasome activation is also responsible for vascular endothelial dysfunction in diabetes.…”
Section: Discussionmentioning
confidence: 98%
“… 116 , 117 A recent study has demonstrated that α-mangostin treatment inhibits LPS-induced increase of NLRP3, ASC, and pro-Caspase-1 expression, as well as IL-1β and IL-18 production, suggesting α-mangostin exerts a protective effect on LPS-induced NLRP3 inflammasome of NP cells. 102 …”
Section: Potential Therapeutic Strategies For Ivdd Via Targeting Pyro...mentioning
confidence: 99%
“…A recent investigation revealed that NF-kB signaling is required for NLRP3 inflammasome activity (Zhang et al, 2019;. As a transcription factor, NF-kB probably mediates the transcription of pro-IL-1b and pro-IL-8, which are necessary for NLRP3 inflammasome activity (Chen et al, 2022). In addition to NLRP3 inflammasome, schistosome eggs can induce NLRP6 inflammasome activation in DCs, which also results in IL-1b production (Sanches et al, 2020).…”
Section: Nlr-dependent Innate Immune Signalingmentioning
confidence: 99%